The Features of the National School of Radar Space Control Systems - Lavrich, Yu.M.; Netak, B.B.; Plaksin, S.V.; Pyaskovsky, D.V. (Science and Innovation, 2024)
Introduction. Ukraine has a space monitoring system implemented based on the Dnieper radar that provides continuous space monitoring. Problem Statement. Radars of this type are large complicated high-tech engineering systems. The novelty of applied R&D solutions, long terms of radar station design and manufacture unable applying the existing development and production standards and, therefore, require creating new ones. Purpose. The purpose is to analyze and to summarize the features of development and manufacture of space control systems based on national radar facilities. Materials and Methods. The systematic analysis of the peculiarities of the Ukrainian school of radar control systems for outer space has been applied using the R&D and the Chief Designer tools for more effectively solving specific problems related to creating new generations of radar stations. Results. It has been shown that in order to realize the information received by the existing radar, it is necessary to ensure its competitiveness in the growing market of such services, which is possible through both upgrading the existing facilities and developing new ones. Taking into consideration the specific features that inevitably manifest themselves at different stages of the radar life cycle, the sufficient R&D groundwork and the experience of creating radars of both the current and the future generations, a number of proposals on effective solution of problems concerning the space monitoring with radar facilities have been presented. Conclusions. To ensure the integration and to supply domestic science-intensive radars to international structures for monitoring outer space (MOS) is impossible unless the existing R&D groundwork is effectively used and the capacity of existing facilities is permanently built up, taking into account the MOS radar specific features. The outlined peculiarities of possible problems and ways of their effective solution can be useful to designers of complex high-tech systems.